Review on the Status and Geographical Distribution of Invasive Alien Plant Species in Bhutan - , Nythri Tshering; , Namgay Rinchen (Archives of Current Research International, 2025)
Invasive Alien Plant Species (IAPS) are non-native, naturalized plants with high potential to spread over large areas at considerable distances. Considering its driving factor and adverse effect on global biodiversity loss and species extinction, the current study aimed to document the IAPS of Bhutan and its geographical distribution in the country. A total of 136 plant species were enumerated, including 22 major IAPS and 25 IAPS through a literature review. There are 9 IAPS in the country from the list of worlds 100 worst IAS. The families Fabaceae (24) constitute the maximum IAPS followed by Poaceae (20) and Asteraceae (19) respectively. IAPS in Bhutan are mostly herbs (73), followed by grass (23) and tree (15). Currently, IAPS was commonly found distributed on disturbed sites, roadsides, fallows, cultivated areas, and margins of wetlands and forest. Still, there is a need for further IAPS documentation, determination of invasive plant species status, and its impact assessment in the country along with its geographical distribution within the country.